A Generic, Scalable, and Rapid Time-Resolved Förster Resonance Energy Transfer-Based Assay for Antigen Detection—SARS-CoV-2 as a Proof of Concept - Juuso Rusanen (American Society for Microbiology, 2021)
PCR is currently the gold standard for the diagnosis of many acute infections. While PCR and its variants are highly sensitive and specific, the time from sampling to results is measured in hours at best.